"Assessment of relationship between xerostomia and oral health‐related quality of life in patients with rheumatoid arthritis". (22nd August 2017) - Chamani, G; Shakibi, MR; Zarei, MR; Rad, M; Pouyafard, A; Parhizkar, A; Mansoori, M
Abstract : Objective: To determine the relationship between xerostomia and oral health‐related quality of life in patients with rheumatoid arthritis. Materials and Method: Two hundred patients with rheumatoid arthritis were assessed using Fox and OHIP‐14 questionnaires concerning xerostomia and oral health‐related quality of life, respectively. The sum of decayed, missing, and filled teeth (DMFT) was determined via an intra‐oral examination. In addition, intergroup comparisons were evaluated using t test, chi‐square, regression, and Tukey analysis. Result: Among rheumatoid arthritis patients, 51% had been afflicted with xerostomia. We found a statistically significant relationship between xerostomia and oral health‐related quality of life ( p ‐value=.004), as xerostomia cases have significantly worse oral health‐related quality of life. Also, there was a statistically significant association between oral health‐related quality of life and gender as well as DMFT. Conclusion: Because there seem to be a high prevalence of xerostomia in patients with rheumatoid arthritis, screening in such population is highly recommended. Therefore, educational programs and/or workshops should be encouraged among healthcare providers to prevent worsening of oral health‐related quality of life.